P21-activated kinase 5 plays essential roles in the proliferation and tumorigenicity of human hepatocellular carcinoma - Fang Zhe-ping; Jiang Bei-ge; Gu Xue-feng; Zhao Bin; Ge Rui-liang; Zhang Fa-biao (Acta Pharmacologica Sinica, 2016)
Zhe-ping FANG1, #, Bei-ge JIANG2, #, Xue-feng GU3, #, Bin ZHAO3, Rui-liang GE2, *, Fa-biao ZHANG1, * 1Department of Hepatobiliary Surgery, Taizhou Hospital of Zhejiang Province, Wenzhou Medical college, Linhai 317000, China; 2Eastern Hepatobiliary Surgery Hospital, Second Military Medical University, Shanghai 200438, China; 3Clinical Research Center, Affiliated Hospital of Guangdong Medical College, Zhanjiang 524001, China Aim: To investigate the roles of P21-activated kinase 5 (PAK5) in proliferation and tumorigenicity of human hepatocellular carcinoma (HCC). Methods: HCC and matched paraneoplastictis tissue samples were obtained from 30 patients. Human HCC cell lines SMMC7721, HepG2, Hep3B, SK-HEP-1, Huh-7, and liver cell line HL-7702 were examined. The expression of PAK5 gene was studied using real-time qPCR and Western blotting. Cell proliferation was quantified with the MTT assay. Cell cycle was analyzed with flow cytometry. The tumorigenicity of Lv-shRNA-transfected HepG2 cells was evaluated in BALB/cA nude mice. Results: The mRNA level of PAK5 was significantly higher in 25 out of 30 HCC samples compared to the matched paraneoplastic tissues. The HCC cell lines showed varying expression of PAK5 protein, and the highest level was found in the HepG2 cells. PAK5 gene silencing in HepG2 cells markedly reduced the cell proliferation and colony formation, and induced cell cycle arrest in the G1 phase. Furthermore, PAK5 gene silencing suppressed the tumor formation in nude mice, and significantly decreased the expression of HCC-related genes Cyclin D1 and beta-catenin. Conclusion: PAK5 may play essential roles in the initiation and progression of human HCC. Thus, it may be an effective therapeutic target or perhaps serve as a clinical diagnostic or prognostic marker in human HCC. Keywords: P21-activated kinase 5 (PAK5); human hepatocellular carcinoma; HepG2 cell; Cyclin D1; beta-catenin; cell cycle arrest; cell proliferation; tumorigenesis; gene silencing This study was supported by the Science Technology Program of Zhejiang Province on the Scientific Research Project (2009C33SA800006), the National Natural Science Foundation of China (30872989), and the Scientific Research Foundation for the Junior Teachers of Medicine in the Second Military Medical University (2011QN20). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail fabiaozhang@yahoo.cn (Fa-biao ZHANG); ruiliangge@yahoo.cn (Rui-liang GE) Received 2012-10-11 Accepted 2013-03-08